Two-step work-hardening and its gigantic toughening effect in Zr-based bulk metallic glasses. (June 2018) - Wang, Tuo; Si, Jiajia; Wu, Yidong; Lv, Kuang; Liu, Yanhui; Hui, Xidong
Abstract: In this work, a two-step work-hardening phenomenon during the compressive deformation process of Zr57.75– x Cu21.15 Fe4.7 Al9.4 Nb6 Co x Mo1 ( x = 1, 2, 3) bulk metallic glasses (BMGs) has been found for the first time. This novel work-hardening mode remarkably improves the deformability and the toughening of these BMGs. It has been evidenced that the secondary stage of work-hardening contributes as high as 60% of total strengthening and 75% of plasticitizing for the BMG with x = 3. The underlying mechanism for the two-step work-hardening has been clarified as the phase separation for first step followed by the nanocrystallization around the shear bands induced by continuous compression deformation. Graphical abstract: Unlabelled Image